Waqf Productivity in Indonesia: Challenges and Prospects for Sustainability - Uyun, Linatul; Hamida, Nuriya (Qanun: Jurnal Hukum Keluarga Islam, 2024)
Islam emphasises the values of social care and sustainability in helping others. This is realised by the practice of waqf, which is then a form of charity. Waqf management that used to focus only on worship purposes is now innovating to a productive management system. The productive concept is expected to improve the welfare of the people and the economy. The purpose of this research is to explain that the concept of productive waqf has not been widely practised by Indonesian Muslims. This research is a literature research, with a normative approach. The normative approach is an approach based on legal norms and the concept of sharia. The result of this research is productive waqf as a more effective form of zakat distribution. Productive waqf is not only an integral aspect of Islamic teachings, but also an effective instrument for building a just, equitable, and sustainable society. Productive waqf so far still faces various challenges, including in terms of management aspects that tend to focus on the use of worship. In addition, there is still a lack of waqif information that assets that can be waqfed are not always immovable objects and no less important the role of the government is still very lacking which then has an impact on the low awareness of waqf.